Thermal evolution offsets the elevated toxicity of a contaminant under warming: A resurrection study in Daphnia magna. (7th May 2018) - Zhang, Chao; Jansen, Mieke; De Meester, Luc; Stoks, Robby
Abstract: Synergistic interactions between temperature and contaminants are a major challenge for ecological risk assessment, especially under global warming. While thermal evolution may increase the ability to deal with warming, it is unknown whether it may also affect the ability to deal with the many contaminants that are more toxic at higher temperatures. We investigated how evolution of genetic adaptation to warming affected the interactions between warming and a novel stressor: zinc oxide nanoparticles (nZnO) in a natural population of Daphnia magna using resurrection ecology. We hatched resting eggs from two D. magna subpopulations (old: 1955–1965, recent: 1995–2005) from the sediment of a lake that experienced an increase in average temperature and in recurrence of heat waves but was never exposed to industrial waste. In the old "ancestral" subpopulation, exposure to a sublethal concentration of nZnO decreased the intrinsic growth rate, metabolic activity, and energy reserves at 24°C but not at 20°C, indicating a synergism between warming and nZnO. In contrast, these synergistic effects disappeared in the recent "derived" subpopulation that evolved a lower sensitivity to nZnO at 24°C, which indicates that thermal evolution could offset the elevated toxicity of nZnO under warming. This evolution of reduced sensitivity to nZnO under warming could not be explained by changes in the total internal zinc accumulation but was partially associated with the evolution of the expression of a key metal detoxification gene under warming. Our results suggest that the increased sensitivity to the sublethal concentration of nZnO under the predicted 4°C warming by the end of this century may be counteracted by thermal evolution in this D. magna population. Our results illustrate the importance of evolution to warming in shaping the responses to another anthropogenic stressor, here a contaminant. More general, genetic adaptation to an environmental stressor may ensure that synergistic effects between contaminants and this environmental stressor will not be present anymore.